2014
DOI: 10.1111/gcb.12768
|View full text |Cite
|
Sign up to set email alerts
|

Multimodel ensembles of wheat growth: many models are better than one

Abstract: Crop models of crop growth are increasingly used to quantify the impact of global changes due to climate or crop management. Therefore, accuracy of simulation results is a major concern. Studies with ensembles of crop models can give valuable information about model accuracy and uncertainty, but such studies are difficult to organize and have only recently begun. We report on the largest ensemble study to date, of 27 wheat models tested in four contrasting locations for their accuracy in simulating multiple cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
256
3
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 433 publications
(290 citation statements)
references
References 42 publications
14
256
3
5
Order By: Relevance
“…This was especially evident for NEE and LE for rain-fed maize at US-NE3, rain-fed soybean LE, and overall diurnal cycles of H. Unlike in some other previous studies (e.g. Asseng et al 2013Asseng et al , 2015Bassu et al 2014;Martre et al 2015) the ensemble mean did not generally outperform the individual models, which was especially true for the sites with maize and soybean crops, which had few models with crop specificity that had better skills compared to the ensemble mean.…”
contrasting
confidence: 71%
See 2 more Smart Citations
“…This was especially evident for NEE and LE for rain-fed maize at US-NE3, rain-fed soybean LE, and overall diurnal cycles of H. Unlike in some other previous studies (e.g. Asseng et al 2013Asseng et al , 2015Bassu et al 2014;Martre et al 2015) the ensemble mean did not generally outperform the individual models, which was especially true for the sites with maize and soybean crops, which had few models with crop specificity that had better skills compared to the ensemble mean.…”
contrasting
confidence: 71%
“…Ryan et al 1996;Amthor et al 2001;Grant et al 2005), and agricultural (e.g. Semenov et al 1996;Frolking et al 1998;Ciais et al 2010;Asseng et al 2013Asseng et al , 2015Bassu et al 2014;Martre et al 2015) ecosystems. Semenov et al (1996) compared the performance of five wheat models at two sites in Europe: Rothamsted, United Kingdom, and Seville, Spain.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One approach with crop models has been to identify models that have similar equations for underlying processes, such as photosynthesis. In general, however, it has not been found that structural similarity leads to similarity in simulated values in crop MMEs (Palosuo et al 2011;Martre et al 2015;Li et al 2015). An alternative approach, proposed for climate models (Bishop and Abramowitz 2013), is to examine the covariance in model errors as the measure of model dependence.…”
Section: Evaluating the Degree Of Relatedness Of The Models In A Mmementioning
confidence: 98%
“…Ensembles allow one to obtain a probability distribution instead of a point prediction (Harris et al 2010). Furthermore, it has been empirically observed in many fields that ensemble averages or medians often better reproduce observations than even the best individual model (Hagedorn et al 2005;Tebaldi and Knutti 2007;Palosuo et al 2011;Martre et al 2015). Additional benefits from working with ensembles of models arise from the closer collaboration between modeling groups.…”
Section: Introductionmentioning
confidence: 99%